Immunosuppressive effects of arsenic in broiler chicks exposed to Newcastle disease virus. (1st November 2016) - Sattar, Adeel; Khan, Ahrar; Hussain, Hafiz Iftikhar; He, Cheng; Hussain, Riaz; Zhiqiang, Shen; Saleemi, Muhammad Kashif; Gul, Shafia Tehseen
Abstract: To assess the effects of prolonged exposure to arsenic (As, as arsenate) on host immune competence overall and resistance to Newcastle disease (ND) viral infection in particular, a study was carried out in broiler chicks. At 7 days of age, chicks were assigned to groups that would undergo varying vaccination, challenge, and/or As exposures; Group 1 was a control; Group 2 was to receive Newcastle disease virus (NDV) only; two groups (Groups 3, 4) were to be given As daily (50 mg/kg, by gavage) from Days 7–35 of the experiment. All groups underwent normal vaccination on Days 5, 23, and 32 against live NDV (B1 type, LaSota strain); two groups (Groups 2, 4) were challenged with field-isolated NDV at Day 24. At Days 14, 21, 28, and 35 of age, subsets of chicks in each group were evaluated. The results showed feed intake and weight gain were lower in As-treated and NDV-challenged chicks. In As-treated chicks, absolute and relative spleen weights were significantly greater, whereas those of the thymus significantly lower, over the entire 35-day period. Effects on bursa weights (absolute, relative) were only significantly reduced through Day 21. Antibody titers against ND were significantly reduced (vs. control) over the whole 35 days in birds that received As alone, but only significantly depressed through the first 21 days in birds that received As + NDV; thereafter, titers were significantly greater (in parallel with effects in birds that received NDV alone). In contrast, antibody responses to T-dependent antigen (Sheep red blood cells [SRBC]) were significantly lower in As only- and As + NDV-treated chicks throughout the study period. Among birds exposed to As (alone or with NDV), in situ phagocytic activity was elevated and cutaneous sensitivity responses decreased during the period from Day 28 to Day 35. NDV alone had spurious effects on phagocytic activity but did cause significant reductions in cutaneous sensitivity responses. It was concluded that arsenic decreased immunity in broiler chicks, thereby making them prone to ND.